Mortalidade aguda em Tamandua tetradactyla(Linnaeus, 1758) - Sousa, Mônica Shinneider de (2018)
The anteaters is one of the Brazilian fauna species most susceptible to trampling, predatory hunting, and loss of habitat following deforestation, often found in rehabilitation programs. In this context, identifying the diseases that can affect this species becomes necessary to guarantee sanity and make possible an adequate return to nature. The objective of this study was to identify the causes of sudden death in captive-bred anteaters, or from seizures of animal traffic in the state of Paraíba, Brazil. In order to do so, the files referring to the files and reports of necropsy of the animals sent to the Laboratory of Veterinary Pathology of the Federal University of Paraíba (LPV / UFPB) between May 2013 and May 2017 were reviewed. Information regarding epidemiological, laboratory findings complementary, clinical and pathological. 12 anteaters, referred after sudden death, were analyzed in this study. Of these, seven were females and five were males and, as to age, four were puppies, three were young and five were adults. The diagnosis was made using the following categories: bacterial (3), parasitic (2), metabolic (1) diseases caused by physical (3) or inconclusive agents (4). Leptospirosis, parasites by Physaloptera magnipapilla and cestodes of the genus Mathevotaenia and musculoskeletal traumas are among the verified conditions. Diagnosis was not possible only when the cadaver was in a marked degree of autolysis. Little anteaters may be the target of sudden-onset diseases, with no history of apparent clinical manifestations, indicating the importance of performing complementary laboratory tests, parasitological, and the determination of anti-leptospiral antibody titres in animals recently introduced in centers of rehabilitation or kept zoological.